Fruit Quality of Different Mango (Mangifera indica L.) Cultivars Grown in the Foothills of Shiwaliks - Yadav, Shailendra Kumar; Homa, Fozia; Prasad, Ram; Kumar, Pramod (Journal of Postharvest Technology, 2013)
The present study describes the post-harvest evaluation of eight mango  (Mangifera indica L.) cultivars viz., Dashehari, Langra, Chausa, Safeda,  Ramkela, Sinduri, Amrapali, Mallika being grown in the eroded soils of the  foothills of Shiwaliks. Plantation of uniform sized plantlets of different  cultivars was raised under uniform edaphic conditions in the Research farm of  ICAR-Indian Institute of Soil and Water Conservation, Research Farm,  Panchkula (Haryana), India in year 2000. Postharvest evaluation of different  cultivars was carried out for the year 2008, 2009 and 2010. Data for the  different post-harvest quality parameter were recorded. The lowest cumulative  yield of 3 years crop war 28.7 kg tree-1 which was recorded for the cultivar  Sinduri whereas the highest yield was recorded for the cultivar Mallika.  Physiologically matured and ripe fruits were utilized for physical–biochemical  analysis. The qualitative analysis of fruits indicated the superiority of hybrid  Mallika in terms of total soluble solids, titrable acidity, TSS: acid ratio, sugar  content, stone, peel and pulp attributes and lowest percent physiological loss in  weight during ripening in comparison to other cultivars evaluated in the study.
Keywords: Mallika; Amrapali; Characteristics; Varietal evaluation Fruit yield